Power converters for grid integration of photovoltaic power system - Cheng, Hei Yuet. (2012)
In a modern and thriving economy, a constant source of energy supply is required for long-term sustainability and survivability. However the current existing source of energy supply, mainly burning of fossil fuels, is not only limited in supply but polluting in nature. A clean and abundant source of energy that can produce electricity without polluting the environment is required in the long-term. Thus, there is the recent emphasis of renewable energy technology in our society.